2021
DOI: 10.1111/1759-7714.13942
|View full text |Cite
|
Sign up to set email alerts
|

Clinical recommendations for perioperative immunotherapy‐induced adverse events in patients with non‐small cell lung cancer

Abstract: Perioperative adjuvant treatment has become an increasingly important aspect of the management of patients with non‐small cell lung cancer (NSCLC). In particular, the success of immune checkpoint inhibitors, such as antibodies against PD‐1 and PD‐L1, in patients with lung cancer has increased our expectations for the success of these therapeutics as neoadjuvant immunotherapy. Neoadjuvant therapy is widely used in patients with resectable stage IIIA NSCLC and can reduce primary tumor and lymph node stage, impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…At the same time, it is also suggested that it is necessary to carry out health education on early pulmonary rehabilitation for lung cancer patients and to develop individualized intervention measures to improve patients' respiratory limitation, relieve physical discomfort, and improve psychological pleasure. (2) e most significant factor in actual problems is taking care of children (r � 0.228, P < 0.001), and the most significant factor in family communication problems is communication with parents (r � 0.151, P < 0.001).…”
Section: Analysis Of Related Factors Of Psychological Distress In Pat...mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, it is also suggested that it is necessary to carry out health education on early pulmonary rehabilitation for lung cancer patients and to develop individualized intervention measures to improve patients' respiratory limitation, relieve physical discomfort, and improve psychological pleasure. (2) e most significant factor in actual problems is taking care of children (r � 0.228, P < 0.001), and the most significant factor in family communication problems is communication with parents (r � 0.151, P < 0.001).…”
Section: Analysis Of Related Factors Of Psychological Distress In Pat...mentioning
confidence: 99%
“…At present, perioperative treatment of lung cancer (preoperative neoadjuvant therapy and postoperative adjuvant therapy), as an important adjuvant method for surgery, has become an increasingly important part of the whole management of non-small-cell lung cancer (NSCLC). With the development of perioperative treatment methods to bring better efficacy and survival benefits to patients, there are also related adverse reactions such as delayed surgery, loss of surgical opportunities, and risk of death [ 2 ]. Therefore, patients with lung cancer in the perioperative period suffer from a series of psychological pressures when faced with problems such as surgical methods, treatment effects, and postoperative rehabilitation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies may have a substantial impact on the clinical management of patients with resectable NSCLC after surgery. Despite the promising results of perioperative ICIs therapy, several questions have yet to be addressed, including irAEs, which can be serious, and in a few cases, even lifethreatening, resulting in inoperability, delayed surgery, or increased chance of postoperative complications (16). Before starting ICIs, physicians should assess patients' possible risk factors such as autoimmune disease, immunodeficiency disease, and significant infection history.…”
mentioning
confidence: 99%
“…The studies to date suggest that neoadjuvant immunotherapy in patients with operable early-stage NSCLC is relatively safe, with incidences of any-grade and ≥3 grade irAEs of 23-57% and 4.5-13%, respectively. However, these are mostly phase I/II studies with a small sample size and short observation time (16). Large-scale prospective studies with sufficient observation periods are necessary to identify potential risk factors associated with perioperative irAEs.…”
mentioning
confidence: 99%
“…The recent expert opinion publication in Thoracic Cancer offers a comprehensive review of existing clinical trials employing neoadjuvant and adjuvant ICI AE chemotherapy, as well as an assessment and recommended treatment of related irAES. 6 While the American Society of Clinical Oncology guidelines 7 focus on irAEs across all cancer types, primarily in late-stage disease, this publication focuses only on patients with lung cancer and specifically those for whom surgery is part of the treatment plan. Heretofore, the more common irAEs observed in neoadjuvant monotherapy ICI studies include endocrinopathies, pneumonitis, and rash.…”
mentioning
confidence: 99%